Towards a new liberal internationalism the international theory of J.A. Hobson - Long, David (LSE monographs in international studies, 1996)
This is a comprehensive analysis of J. A. Hobson's writings on international relations. Hobson is most famous for developing the neo-Marxist theory of imperialism, but in this book David Long argues that Hobson was also a key figure in the history of liberalism. He shifted liberal international theory away from its laissez-faire origins towards a focus on international organization, making him a forerunner of the functional approach in international relations. The book outlines the philosophical outlook and political economy which informed Hobson's theory, and challenges the narrow interpretation of imperialism which has dominated international relations. Setting out the sources of and contradictions within Hobson's proposals for international government, this book is a contribution not only to the study of international relations, but also to the history of political thought and British liberalism